2018
DOI: 10.5016/geociencias.v37i1.12212
|View full text |Cite
|
Sign up to set email alerts
|

Análisis Morfotectónico en El Piedemonte Suroccidental Del Antepais Andino, Sierras Pampeanas Occidentales, San Juan, Argentina

Abstract: El retroarco andino, entre los 27°S y 33°S, se caracteriza por ser una de las regiones con mayor sismicidad cortical en el mundo, siendo epicentro de importantes terremotos en el territorio argentino. Esta sismicidad produce una intensa deformación, provocando cambios en la morfología del terreno. En el sector occidental de Sierras Pampeanas Occidentales, en la sierra de la Huerta, se utilizó un SIG para diferenciar unidades geomorfológicas y determinar parámetros cualitativos y cuantitativos que permitieran c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…For these reasons, we conducted our study on the prominent cumulative scarps of the Pan de Azúcar fault strand (Figures 2-5) where conditions are suitable for determining short-and longterm slip rates through TCN surface exposure dating and measurement of fault offset. At the southern tip of the range, Rothis et al (2018) reported Quaternary alluvial surfaces offset by the LCFZ (Figure 3); Rothis et al (2019) measured slip rates by optically stimulated luminescence (OSL) dating of some displaced alluvial deposits.…”
Section: Las Chacras Fault Zonementioning
confidence: 99%
“…For these reasons, we conducted our study on the prominent cumulative scarps of the Pan de Azúcar fault strand (Figures 2-5) where conditions are suitable for determining short-and longterm slip rates through TCN surface exposure dating and measurement of fault offset. At the southern tip of the range, Rothis et al (2018) reported Quaternary alluvial surfaces offset by the LCFZ (Figure 3); Rothis et al (2019) measured slip rates by optically stimulated luminescence (OSL) dating of some displaced alluvial deposits.…”
Section: Las Chacras Fault Zonementioning
confidence: 99%